In this Issue - David Briggs (ACHSM, 2019)
This issue is a Special Issue in that it predominantly features a series of articles that have arisen from the CPCE Health Conference 2019. The special issue commences with an editorial where Professor Yuen emphasises the ongoing collaboration with this Journal, the ACHSM and the Hong College of health Services Executives and with the CPCE. His leadership and contribution are appreciated. The first article of the Special Issue is by Hasegawa, Matsumoto, and Hirata of Toho University Tokyo Japan who present an article entitled 'Aging and Diversity of Medical Needs: Cost of Illness of Cerebrovascular Disease in Each Prefecture of Japan. This is followed by the contribution from Ng, Fong and Kwong of Hong Kong on the 'Transition of hospital acute-centric to long term care in an ageing population in Hong Kong - is it an issue of service gap'. In the next article, Chu and Chong of Hong Kong address the 'Oncology Pharmacist's role and the impact on multidisciplinary patient-centred practice of oncology clinic in public hospitals in Hong Kong. Two interesting articles follow from Kwan, Yick and Wong of the Institute of Textiles and Clothing, Hong Kong Polytechnic University of Hong Kong who provide a research article on the 'Impact of Co- creation Footwear Workshops on Older Women in Elderly Centres in Hong Kong' and the following article from Yick, Yip and Ng, again from the Institute of Textiles and Clothing and from the Division of Science and Technology of the Hong Kong College of the same University. The latter article examines the importance of thermal comfort in foot wear design for the elderly and is entitled 'Thermal equations for predicting foot skin temperature'. In conclusion, Kwong and Fong provide a review article on a contemporary issue of 'promotion of appropriate use of electronic devices among Hong Kong adolescents. We thank Professor Yuen and his authors for this important contribution to our understanding of humane, wholistic and integrated care from diverse international health systems.   In support of this effort of our colleagues above, we have added some more articles ready for publication. This includes an editorial on Health Reform that was prompted by my plenary session contribution at the CPCE Hong Kong Conference. We also continue the international emphasis of this issue with a contribution from Sharma of Maharishi Markandeshwar University, Northern India with a research article on the 'Extrinsic Rewards, Occupational Commitment, Career Entrenchment and Career Satisfaction of Dentists'. Our next article is by Mak and colleagues in a research article entitled 'What is the Professional Identity of Allied Health Managers?' Isouard and Martin provide a further contribution about the Australian workforce in an article entitled 'Managers of aged care residential services: 2006-2016.' Way and colleagues conclude this issue with an analysis of management practice in one local health district in Australia entitled 'The pursuit of purposeful partnerships-making a health matrix successful'.